Greening of Petroleum Operations : the Science of Sustainable Energy Production. - Islam, M. R. (John Wiley & Sons, 2010)
This state-of-the-art text covers some of the most hot-button issues in the energy industry, covering new, greener processes for engineers, scientists, and students to move petroleum operations closer to sustainability. Petroleum is still the world's most diverse, efficient, and abundant energy source, however, due to grim climate concerns and high gas prices, there is a growing initiative from global leaders of petroleum to "go green." This book investigates and details how to do that